Smokers' hair: Does smoking cause premature hair graying? - Ayman A Zayed; Awni D Shahait; Musa N Ayoub; Al Motassem Yousef (Wolters Kluwer Medknow Publications, 2013)
Aims: To determine if there is a significant association between premature hair graying and cigarette smoking. Materials and Methods: A cross-sectional observational study was conducted in a nonclinical setting on 207 participants on August 24 until 25, 2010. Participants were classified into two groups [premature hair graying (PHG) and normal hair graying]. PHG was defined as the first appearance of gray hair before the age of 30. Data were collected using an interview questionnaire and measurements of body mass index, waist circumference, fasting blood glucose and blood pressure. Collected data were statistically analyzed using SPSS 16, Chicago, IL. Results: Of the 207 subjects, 104 (50.2%) had first appearance of gray hair before the age of 30 (PHG group) while the other 103 (49.8%) were considered normal hair graying group. The prevalence of smokers in the "PHG" group was higher (40.2% vs. 24.7%, P = 0.031). Smokers had earlier onset of hair graying (smokers: 31 (7.4) vs. nonsmokers: 34 (8.6), P = 0.034). Using multiple logistic regression with conditional likelihood, smokers were two and half times (95% CI: 1.5-4.6) more prone to develop PHG. Conclusion: This study suggests that there is a significant relation (with adjusted odds ratio of two and half) between onset of gray hair before the age of 30 and cigarette smoking.